Female subjectivity in times of constraint: a study of Naguib Mahfouz and Gabriel García Márquez - Mahmoud, Safinaz Ahmed Saad (AUC Knowledge Fountain, 2015)
This study aims at examining the depiction of female characters in two postcolonial novels set in the mid-twentieth century, namely, Naguib Mahfouz’s The Beginning and the End and Gabriel García Márquez’s Chronicle of a Death Foretold. Critic Gayatri Chakravorty Spivak’s theory of the silent female subaltern poses a challenge to reading the (hi)story of any female character when the narrator assumes a dominant role in the literary narrative. Research in this thesis extends Spivak’s dichotomy of silence and speech to accommodate a middle ground that allows us read the characters’ presence as speaking voices of their (hi)stories. While Spivak is interested in how Western feminists approach to third-world woman, this work offers a variation on this inquiry, asking whether it is possible for third-world women in their fictional writings to retain limited autonomy, while constraints are nonetheless imposed on them by male narrators. Specifically, I ask if it is possible for Mahfouz and Márquez to represent the female subaltern without fully sustaining a patriarchal perspective in both literary works. This examination concludes that both male authors succeed at providing Nefisa and Angela, main female figures, with a limited subjectivity that gives voice to the often marginalized in the history of postcolonial worlds, and reflects the limitations of their societies’ convictions towards woman.